2008
DOI: 10.1038/sj.bjc.6604275
|View full text |Cite
|
Sign up to set email alerts
|

Parity and breastfeeding are protective against breast cancer in Nigerian women

Abstract: As the relation between reproductive factors and breast cancer risk has not been systematically studied in indigenous women of subSaharan Africa, we examined this in a case -control study in Nigeria. In-person interviews were conducted using structured questionnaires to collect detailed reproductive history in 819 breast cancer cases and 569 community controls between 1998 and 2006. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CI). Compared with women with menarcheal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 17 publications
11
102
2
5
Order By: Relevance
“…13 The present findings indicate menarche age also relates to mammography history, with previous mammograms more likely in women of a younger menarche age. Again, this arguably depicts efforts by health providers to increase breast cancer awareness or deliberate efforts by the women themselves to seek mammography (given their elevated risk) in response to the health promotion jingles.…”
Section: Educational Implications For Age At Menarchementioning
confidence: 63%
See 1 more Smart Citation
“…13 The present findings indicate menarche age also relates to mammography history, with previous mammograms more likely in women of a younger menarche age. Again, this arguably depicts efforts by health providers to increase breast cancer awareness or deliberate efforts by the women themselves to seek mammography (given their elevated risk) in response to the health promotion jingles.…”
Section: Educational Implications For Age At Menarchementioning
confidence: 63%
“…12 Research also suggests age at menarche is critical in Nigerian women with younger age at first menstruation being associated with elevated breast cancer risk. 8,13 Finally, age at menopause has also been implicated in breast cancer risk, with older age at menopause being associated with greater risk. 14 Given the early onset of breast cancer in African women, there is a need to better understand the link between age-related risk factors and mammography uptake in this population.…”
Section: Age-related Risk Factorsmentioning
confidence: 99%
“…Em um estudo caso-controle desenvolvido na Nigéria com uma amostra de 819 casos e 569 controles, pesquisadores encontraram uma redução de 7% no risco de desenvolver esse tipo de câncer a cada aumento de 12 meses no tempo de amamentação (OR=0,93; IC95% 0,87-1,0) 11 . Uma possível explicação para esse fato é que durante a amamentação ocorrem períodos de baixa exposição ao estrógeno e tal hormônio está intimamente envolvido na carcinogênese da doença 12 .…”
Section: Discussionunclassified
“…Women in the lowest socioeconomic groups were the most likely to breastfeed exclusively likely due to cultural factors that incentivize breastfeeding and financial constrains that limit access to infant formula (Huo et al, 2008;Smith-Oka, 2009). Prior studies in Colombia found that woman with higher levels of education were more likely to stop exclusive breastfeeding and introduce artificial infant formula due to the constraints of maternal leave and the need to return to the workplace (Niño, 2014).…”
Section: Discussionmentioning
confidence: 99%